Impacto de la titulación colectiva en el consejo comunitario de Lloro-Cocoillo Choco Colombia 2012 (2013)
In this research work was carried out an analysis of the impact of collective ownership, based on Law 70 of 1993, the Consejo Comunitario Integral de Lloro Cocoillo (Choco Colombia). A notice of the social, economic, political and cultural development of the Consejo Comunitario, forging a global picture of the development of this community for the recognition of the right to collective ownership of black communities, where paperwork must be filled bill extending the Decree 1745 of 1995, article 20, for the collective titling of the lands they inhabit.